THE NEOPROTEROZOIC KOLET UM KHARIT BIMODAL METAVOLCANIC ROCKS, SOUTH EASTERN DESERT, EGYPT: A CASE OF ENRICHMENT FROM PLUME INTERACTION? - Farahat E.S. (My University, 2006)
Neoproterozoic metavolcanic rocks of Kolet Um Kharit (KUKh) in the southern Eastern Desert of Egypt have been traditionally regarded as a bimodal island-arc sequence. However, geological and geochemical arguments presented here make this interpretation doubtful. Geochemically, these rocks are classified into mafic (tholeiitic basalts) and felsic (high-K rhyodacites to rhyolites) groups. Both the KUKh mafic and felsic metavolcanic rocks show similar geochemical characteristics, implying a genetic link. They have comparable trace element ratios, such as Zr/Nb (27–30 vs. 20–36), Y/Nb (5.44–6.25 vs. 5.05–5.9), K/Rb (577–1164 vs. 573–937), Ba/La (4.29–25–9 vs. 11.4–16.2), Nb/Yb (1.82–2.03 vs. 1.76–1.99). Similarly both groups have parallel LREE-enriched patterns (La/YbCN=2.37–2.81 vs. 2.55–3.17); and negative Nb and Ta anomalies (Nb/Lapm=0.51–0.58 vs. 0.45–0.52 and Ta/Lapm=0.51–0.62 vs. 0.49–0.55). The observed negative Nb and Ta anomalies in the KUKh metavolcanic rocks cannot be attributed to crustal contamination or fractional crystallization. These rocks could represent either a remnant of break-up LIP or were derived from an enriched mantle source containing subduction components beneath an intraoceanic back-arc basin. The recognition of the KUKh rocks as derived from an enriched mantle source revives interest in models that involve enrichment from “plume” interaction during the evolution of the Arabian-Nubian Shield.
Keywords: ARABIAN-NUBIAN SHIELD; EGYPT; NEOPROTEROZOIC; PAN-AFRICAN; VOLCANIC GEOCHEMISTRY; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская